Supporting the Educational Process with Board Games Based on the Example of the Community in Action Game - Bernatowicz, Anna; Rataj, Zuzanna (Studia Oeconomica Posnaniensia, 2015)
This paper discusses the use of board games in supporting the educational process in the constructivist approach. Using the example of the Community in Action board game, it shows how the use of this type of game fits into the classroom formula based on D. Kolb's learning model. The article describes the rules of the game, its technical aspects, the tasks facing the players (learners), and the gameplay. Additionally, it identifies the main contents which are taught through the use of the game with regard to two subjects taught as part of the Social Policy programme at the Poznań University of Economics. Based on a survey conducted among students as well as through participant observation, the authors analyse the effects of using board games as a didactic tool and identify the roles of the teachers who use them in the classroom.